PERUMUSAN PENGUKURAN TINGKAH LAKU IMPROVEMENT (KAJIAN EMIPIRIS PADA SURVIVOR BANTUL, YOGYAKARTA) - Ayu Dwi Nindyati (Universitas Padjadjaran, 2012)
The purpose of this research was creating the improvement behavior construct for community. This construct was adapted from performance improvement construct in industrial and organizational field. The improvement behavior also developed three activities dimension such as planning, create and implementation of strategy to solve the problems. The research method was quantitative-descriptive with focus group discussion and questionnaire to collect the data. The respondents were earthquake survivor from Bantul, Yogyakarta. The result of the data analysis was the construct of performance improvement could be use to explain the improvement behavior in community. The plan dimension was the smallest loading factor to improvement behavior.